2015
DOI: 10.15345/iojes.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Personal Self-Concept as Mediator and Moderator of the Relationship between Insight and Psychological Vulnerability

Abstract: In this study, the mediator and moderator effects of personal self-concept on the relationship between insight and psychological vulnerability were investigated. The participants were 322 university students attending different departments at Kocaeli University in Turkey. Data were collected by using the Insight Scale, the Psychological Vulnerability Scale and the personal selfconcept Scale. Data were analyzed via Hierarchical Regression Analysis. The statistical analyses of the data by using "SPSS for Windows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…Second, the construct validity of the Portuguese version of the PVS confirms the original six-item unidimensional structure, in accordance with previous literature (Akın, Demirci, & Yıldız, 2015;Rueda et al, 2007;B. Satici et al, 2014;Selbie et al, 2004;Sinclair & Wallston, 1999, 2010.…”
Section: Discussionsupporting
confidence: 89%
“…Second, the construct validity of the Portuguese version of the PVS confirms the original six-item unidimensional structure, in accordance with previous literature (Akın, Demirci, & Yıldız, 2015;Rueda et al, 2007;B. Satici et al, 2014;Selbie et al, 2004;Sinclair & Wallston, 1999, 2010.…”
Section: Discussionsupporting
confidence: 89%
“…This mediation pattern means that the higher the students' selfconcept, the higher the support of the school climate that students feel, which has an impact on students' high academic optimism. That statement is in line with research conducted by Akın et al (2015), explaining that self-concept has a mediating role towards psychological outcomes, where personal self-concept plays an important role as a mediator between psychological insight and vulnerability. If students have a high level of understanding by a high self-concept, it will also reduce psychological exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Some other researchers found that greater levels of social connectedness and well-being were significantly related to lower levels of depression that might be occurred as result of psychological vulnerability (Armstrong & Ooneb-Early, 2009). Additionally, Akin, Demirci, and Yildiz (2015) suggested that insight, as a positive predictor of psychological well-being (Harrington & Loffredo, 2011), was negatively related to psychological vulnerability. Thus, the findings of the current study are consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%